I will pay someone to do my assignment: an analysis of market demand for contract cheating services on twitter. Issue 4 (18th May 2020) - Amigud, Alexander; Lancaster, Thomas
Abstract: Contract cheating providers exist as businesses with a single shared intention, to profit on a student's inability to fulfil academic requirements for themselves. For contract cheating providers to make money, the correct market conditions are required. First, providers need to be able to offer the expertise that students request. Second, students need to be financially able to pay for specialist support across a diverse range of different areas. If students are unable to meet the price or require expertise that providers do not offer, the transaction is not going to be completed. Therefore, an examination of the demand-side of the contract cheating process in terms of subject matter expertise and the price of offers is important. The research presented in this paper is based on the analysis of 1579 Twitter messages (tweets) that contract cheating providers engaged with. The study aims to examine price variation and the type of assignments students seek to outsource. For typical requests such as essay writing, students are shown to be willing to pay $33.32 per 1000 words. Some services carry a premium, particularly where a student wishes to hire an impersonator to take an examination for them. The student demand for paid help is seen to be highest in the mathematics field, suggesting that students feel under-equipped and under-supported in this area. The paper concludes by discussing further implications of this research and strategies for the minimisation of contract cheating.